2001
DOI: 10.33584/jnzg.2001.63.2422
|View full text |Cite
|
Sign up to set email alerts
|

Damage potential of Argentine stem weevil in Lincoln dairy pasture: has biological control by Microctonus hyperodae altered the balance?

Abstract: To measure the impact of biological control of Argentine stem weevil, Listronotus bonariensis (ASW) by Microctonus hyperodae in dairy pasture, a research site was established in the autumn of 1997 on a dairy farm near Lincoln, where the parasitoid had been present since 1994. Existing pasture was killed with glyphosate and four ryegrass cultivar treatments consisting of three perennial (Nui, Embassy, Vedette) and one hybrid mixture (Marsden/Greenstone), each containing either low or high levels of Neot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The relatively higher numbers of L. bonariensis on wild-type most probably reflected the moderate proportion of endophyte-infected tillers (52%) in these pastures, as AR1 and wild-type infected ryegrass tillers provide an equivalent high level of feeding deterrence to L. bonariensis adults through the production of peramine (Popay et al 2003). Furthermore, ryegrass densities measured in this study were far higher than that measured by Barker et al (1989) in Waikato, but similar to those measured under irrigated pasture in Canterbury (Goldson et al 1998, McNeill et al 2001. Therefore, it is highly probable that in the Wairarapa wild-type pastures, endophyte-free tillers were not limiting to L. bonariensis oviposition and subsequent adult recruitment.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The relatively higher numbers of L. bonariensis on wild-type most probably reflected the moderate proportion of endophyte-infected tillers (52%) in these pastures, as AR1 and wild-type infected ryegrass tillers provide an equivalent high level of feeding deterrence to L. bonariensis adults through the production of peramine (Popay et al 2003). Furthermore, ryegrass densities measured in this study were far higher than that measured by Barker et al (1989) in Waikato, but similar to those measured under irrigated pasture in Canterbury (Goldson et al 1998, McNeill et al 2001. Therefore, it is highly probable that in the Wairarapa wild-type pastures, endophyte-free tillers were not limiting to L. bonariensis oviposition and subsequent adult recruitment.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, low adult numbers were observed in a study examining the relationship between endophyte, L. bonariensis and its parasitoid M. hyperodae (Goldson et al 2000), leading to the suggestion that parasitism may have suppressed weevil numbers. McNeill et al (2001) reported a similar result on a dairy farm near Lincoln, where adult numbers were high in the first summer following pasture establishment (c. 128 /m 2 ) but thereafter, were less than 40 /m 2 .…”
Section: Discussionmentioning
confidence: 59%
“…McNeill et al 1996) or following pasture renewal, as has been observed for the Argentine stem weevil parasitoid in New Zealand dairy pasture (e.g. McNeill et al 2001).…”
Section: Discussionmentioning
confidence: 73%
“…In cooler climates and where there is little pest damage, infection rates in pastures sown as endophytefree can stabilise at low levels (e.g. Eerens et al 1998;McNeill et al 2001McNeill et al , 2007.…”
Section: Persistence Endophyte and Insect Controlmentioning
confidence: 99%